(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The discovery of germ line mutations leading to these cancers and the study of relatively uncommon inherited tumours have been the main areas of molecular genetics’ contribution to colorectal cancer. On the other hand, a lot is now understood about the somatic factors contributing to colorectal cancer in general. The relationship between genetic traits and prognosis has been investigated in several research. This article’s goal is to review these studies and provide an overview of the present state of the field. It is evident that numerous distinct pathways exist for the development of this malignancy, and some molecular characteristics appear to correspond with clinicopathological features, despite the fact that many of the published studies are tiny and inconclusive. Studies are currently limited to analysing a small number of molecular markers, but with the development of techniques for the quick genetic profiling of large numbers of colorectal cancers, it will be possible to comprehensively analyse the therapeutic relevance of a range of colorectal cancer genotypes.